Evaluasi Efektivitas Intervensi Sosialisasi Bahaya serta Penggunaan Alat Pelindung Diri (APD) kepada Pekerja UMKM Logam di Mejobo, Kudus - Charisha Mahda Kumala; Muhammad Navis Mirza; Novi Styaningsih; Siti Rohmatun Nafisah (Journal of Innovative and Creativity, 2025)
Metal MSMEs (micro, small, and medium enterprises) play a significant role in the local economy, but often face unresolved occupational safety issues. This study aims to identify potential occupational risks and evaluate the effectiveness of interventions in the form of hazard socialization and distribution of PPE to metal MSMEs workers in Mejobo, Kudus. The methods used include HIRADC (Hazard Identification, Risk Assessment and Determining Control), interviews, direct observation, noise measurement with a sound level meter, and distribution of the Nordic Body Map questionnaire. The results showed that the noise exceeded the NAB (87.2 dBA), accompanied by high complaints of muscle pain in the back. Socialization and distribution of earplugs were considered effective in increasing worker awareness and comfort. This study emphasizes the importance of collaborative and sustainable K3 education.